2017
DOI: 10.1093/intimm/dxx060
|View full text |Cite
|
Sign up to set email alerts
|

Generation of allo-antigen-specific induced Treg stabilized by vitamin C treatment and its application for prevention of acute graft versus host disease model

Abstract: Antigen-specific regulatory T cells (Tregs) possess the potential to reduce excess immune responses in autoimmune diseases, allergy, rejection after organ transplantation and graft-versus-host disease (GVHD) following hematopoietic stem cell transplantation. Although in vitro-expanded antigen-specific induced Tregs (iTregs) have been considered to be a promising therapeutic agent against such excessive immune reactions, the instability of iTregs after transfer is a fundamental problem in their clinical applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…It is interesting to point out that some clones acquired total demethylation TSDR, so the refinement in their characterization could improve the isolation of stable iTregs with an established TSDR demethylation pattern over the course of the culture. In this context, recent reports have shown that is possible to increase the demethylation status of the TSDR region by adding vitamin C to iTreg cultures (56,57), which was reported to be an activator of TET enzymes, which, in turn, control the stability of FOXP3 (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to point out that some clones acquired total demethylation TSDR, so the refinement in their characterization could improve the isolation of stable iTregs with an established TSDR demethylation pattern over the course of the culture. In this context, recent reports have shown that is possible to increase the demethylation status of the TSDR region by adding vitamin C to iTreg cultures (56,57), which was reported to be an activator of TET enzymes, which, in turn, control the stability of FOXP3 (47).…”
Section: Discussionmentioning
confidence: 99%
“…37 Indeed, in a GVHD murine model, vitamin C stabilizes alloreactive T regulatory cells by demethylation of the FoxP3 promoter, the intronic cis-regulatory elements on DNA molecules. 38 Ascorbic acid is also a cofactor for the enzyme ten-eleven translocation (TET) which mediates promoter hypomethylation of the FOX P3 locus amongst other loci involved in hematopoiesis. 39,40 Huijskens et al showed that AA enhances ex vivo expansion of NK cells in cell culture systems as well as their differentiation from hematopoietic progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…74 Recent studies have demonstrated that demethylation of CNS2 by Tet enzymes is promoted by vitamin C in iTregs, leading to stabilized Foxp3 expression. 17,65,72,74 Vitamin C was shown to potentiate Tet activity, 75,76 thereby facilitating demethylation of the Foxp3 CNS2 region and increasing the stability of Foxp3 expression in TGF-βinduced iTregs. 77 Compared with untreated iTregs, iTregs generated under low oxygen conditions in the presence of vitamin C retained more stable Foxp3 expression in vitro and in vivo and exhibited stronger suppression activity in a colitis model.…”
Section: Treg-specific Epigenetic Modifications and Stability Of Tregsmentioning
confidence: 99%
“…We observed stable, very high FOXP3 expression in human iTregs that underwent vitamin C-treatment. 17 Vitamin C treatment of iTregs also shows promise for innovative clinical applications of adoptive Treg immunotherapy. Further understanding of the mechanisms that facilitate the establishment of a Treg-specific transcriptional program will allow the production of sufficient numbers of antigen-specific Tregs with appropriate stability.…”
Section: Use Of Itregs To Prevent Gvhdmentioning
confidence: 99%
See 1 more Smart Citation